2020
DOI: 10.1093/ehjcr/ytaa224
|View full text |Cite
|
Sign up to set email alerts
|

Management of COVID-19 myopericarditis with reversal of cardiac dysfunction after blunting of cytokine storm: a case report

Abstract: Background Coronavirus disease 2019 (COVID-19) is a syndrome that has been associated with multiple cardiac complications including myopericarditis. The pathophysiology and treatment for myopericarditis in the setting of COVID-19 infection is still under investigation. Case summary We present a case of a 60-year-old male admitted for dyspnoea due to COVID-19. He developed new ST-segment elevation, elevated cardiac enzymes, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 14 publications
0
26
0
5
Order By: Relevance
“…Additionally, compounds must also be evaluated for cellular toxicity. The cytotoxic effect of In addition to inhibition of viral replication, blunting this inflammatory response before overt cytokine storm is important to improve outcomes [7,16,17]. Although remdesivir and convalescent plasma are used for this purpose, there is a need for adjunct treatments to ameliorate disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, compounds must also be evaluated for cellular toxicity. The cytotoxic effect of In addition to inhibition of viral replication, blunting this inflammatory response before overt cytokine storm is important to improve outcomes [7,16,17]. Although remdesivir and convalescent plasma are used for this purpose, there is a need for adjunct treatments to ameliorate disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of this virus include potential effects on the conducting system, 9 development of arrhythmias, 10 coronary artery disease, 11 thrombosis, 12 and myocardial effects. 13 , 14 In addition, there is a suggestion that underlying cardiac disease may contribute to poor outcomes from SARS-CoV2 infection. 15 This collection is an excellent repository demonstrating the clinical effects of COVID-19 on the cardiovascular system.…”
mentioning
confidence: 99%
“…Medications that have been employed so far in pericardial disease related to COVID-19 include colchicine, NSAIDs including aspirin, steroids, and intravenous immunoglobulins (IVIG) [ 6 , 7 , 17 ]. Colchicine has been used alone or in combination with NSAIDs successfully [ 5 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine has been used alone or in combination with NSAIDs successfully [ 5 , 7 , 10 ]. Li et al reported a case of a hemodynamically unstable patient with COVID-19 myopericarditis who responded well to IVIG and methylprednisolone [ 17 ]. At the beginning of the pandemic, there was some safety concern related to NSAIDs use in COVID-19 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%